Desigualdades inter-regionais e políticas públicas para o setor industrial paranaense na década de noventa - Oliveira, Maria Aparecida de (2001)
The State of Paraná since sixty decade, have been building his industrial park, that during 1970s and 1980s was expanded and modernized projecting its economy in paces relatively fast towards more participation in the national race. Throughout of the 1990s, more intensively between 1995-2000, the State Governance has been devoting itself in an industrializing race, competing with other states of the federation aiming to be graced with the biggest fraction of decisions of entrepreneurial investments involving regional choices. With an offensive politics of incentives, Paraná attracted more than two hundred news enterprises. However, most firms are set up in the Curitiba Metropolitan Region or in fewer pole-cities in the state. This concentration model development, that nearly always been applied in the State of Paraná since its threshold, in the ninety decade has intensified seriously. This work consists in describe and analyze interregional inequalities into structure the industrial in Paraná State, and the public politics and government programs and institutions of the industrial supports in State of Paraná in the 90s. Although Hirschman, Myrdal and Perroux's theoretical bases identifing the causes of the highly industrial agglomeration in the Curitiba Metropolitan Region and fewer cities-poles using economic-social index-finger during 1990s; also to diagnose of the structure and dynamic of transformation industry in the twenty-four regions of Paraná; to analyse the public politics and programs of the State Paraná of the others governance and not-governance institutions to industrial development. In conclusion, verified that the industrial conformation é externally corelly in the Metropolitan Curitiba Region and in fewer core-cities, where is concetred the most firms with highly value-added products that retained the most industrial, value-added participation, and for consequence, population concentration. The locacional preference for Curitiba Metropolitan Region and for fewer core-cities is found also in the destination of the public politics and programs of State Paraná's government, and the also in the locazation of universities, research and supports institutions. Conclusion also, that these cities-poles, including the cities located in Curitiba Metropolitan Regiona, are localized on the Road System "Ring of Integration", concentrating the most of industrial firms, industrial outcome, jobs, population, institution and programs of industrial supports. In this "Ring of Integration" there are "Development Axis" composed by pole-cities and industries-key that promote a spatial transmission of growth, through spread effect, that follows the spatial logical way with the vectors of the "Ring of the Integration". In the other side, are the regions and cities without this dynamic, engendering a cumulative and vicious process, with litter number of the firms and products with value-added lower , outmigration population, without teaching institutions and/or courses with industrial emphasis, researches and industrial supports. In this picture, verified that the industrial politics of the State Government and the actions of the institutions have being unable in reversion of the factors that affect the location of new enterprises, demonstrating necessity of a new plan for industrial development connected with regional growth.